FACTORS INFLUENCING BEHAVIOURAL INTENTION OF ACADEMICS IN USING MOODLE: AN APPLICATION OF THE UTAUT MODEL - Oluwafemi Afolabi; Petros N Dlamini; Neil Davies Evans (International Journal of Innovative Technologies in Social Science, 2025)
The study examines factors influencing the behavioural intention and actual usage of Moodle among academics at the University of KwaZulu-Natal (UKZN), South Africa. The study is anchored on the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The research design utilised in this study is quantitative in nature, guided by the survey method where data are collected from 89 academic staff. Data collected are analysed using the Partial Least Squares Structural Equation Modelling (PLS-SEM) technique. The analysis reveals that performance expectancy and social influence are the most relevant determinants of behavioural intention, while facilitating conditions significantly determines actual use. Behavioural intention is also a significant predictor of actual use where higher intentions to use Moodle led to higher usage. Notably, effort expectancy does not impact behavioural intention to use Moodle. Neither gender, age, nor experience, when considered as moderating variables, shows a significant effect on the relationships between constructs. Consequently, the applicability remains consistent across different user groups. The results of this study indicate that interventions aimed at increasing Moodle usage at UKZN, and similar institutions should focus on increasing the perceived usefulness of Moodle, capitalising on positive peer influence, and providing strong support systems. The study also contributes to the validation of the UTAUT model in the South African higher education setting and offers leads that can inform the design and implementation of e-learning strategies for developing countries and the setting of Learning Management Systems (LMS) platforms to maximise educational results.